Examining of crossover instructional strategy toward biology students' academic performance in secondary schools - Nwuba, Izunna Shedrack; Egwu, Sussan Onyebuchi; Awosika, Opeyemi Fadekemi; Osuafor, Abigail Mgboyibo (Univeritas Papua, 2023)
The study investigated how the crossover instructional strategy (CIS) affected secondary school students' biology academic performance in Onitsha Education zone. The non-randomized control group design, a quasi-experimental research strategy, was used in the study. A multi-stage sampling technique was used to choose 52 Senior Secondary Year Two (SS2) students (21 boys and 31 girls) from the 5,132 biology students in the zone. A coin toss was used to assign the sampled students, who were enrolled in two intact classes, to the control (10 males and 15 girls) or experimental (11 boys and 16 girls) groups at random. The researchers created a 50-item biology achievement test (BAT), which has a reliability coefficient of 0.81. The results demonstrated that CIS increased biology students' academic success more than the Conventional Lecture Method (CLM). Biology student academic achievement was unaffected by gender either alone or in combination with the teaching strategies. The research found that CIS is a cutting-edge educational strategy that actively involves students in the learning process in both formal and informal settings, helping them retain biology concepts and ultimately improve their academic performance. In accordance with the findings, the study recommended that biology teachers implement CIS in schools to improve students' biology achievement.